Vulnerability of identity and memory : Jasenovac, Ricoeur, and the death of God - Mladenovska-Tešija, Julijana (Array, 2018)
This paper was created as a result of discussions with the students from the Evangelical Theological Seminary in Osijek, as part of the Introduction into Philosophy course. In the paper we used parts of Luka Đukić’s essay, “Memorial Centers: The Role of Memory,” which have, as part of dialogue regarding the role of memory, been inserted into the text by J. Mladenovska-Tešija. The purpose of the paper is to emphasize the relevance of Ricoeur’s reflections about memory for Evangelical Christians, especially considering Christ’s death on Calvary as an anti-narrative.